Intraosseous Primary Leiomyosarcoma of the Mandible: A Rare Case Report: Primary Leiomyosarcoma of the Mandible - Mashhadiabbas , Fatemeh; Tabrizi , Reza; Alam , Mostafa; Gholami, Sanaz (Journal of Dental School, 2021)
Objectives Spindle-shaped lesions, which include a wide range of reactive lesions from malignant to very invasive, are among the most challenging head and neck pathologies. Herein, we report a case of leiomyosarcoma (LMS) of the mandible for which, immunohistochemistry was performed to find out whether it was a primary or a metastatic tumor. Case This case report presents a 23-year-old female with a 3-month history of pain and mild swelling in the anterior mandible. Panoramic radiography and cone-beam computed tomography revealed an osteodestructive lesion in the mandible. The tumor was composed of interlacing fascicles of spindle-like cells with pleomorphism, hyperchromatism, and atypical mitotic figures. Immunohistochemical (IHC) staining revealed that the tumor cells were positive for vimentin, smooth muscle actin (SMA), desmin, and P53 and had negative reactivity for estrogen receptor (ER) and S100. The patient underwent hemi-mandibulectomy with immediate reconstruction via a microvascular fibula flap. The patient died 15 months after surgery due to metastasis to the right pleura. Conclusion Primary LMS of the jaws is rare and can be confirmed by IHC staining